Empirical futures : anthropologists and historians engage the work of Sidney W. Mintz. - Baca, George; Khan, Aisha, 1955-; Palmié, Stephan (University of North Carolina Press, 2009)
Contributors to this volume address a current methodological crisis in anthropology today by turning to the methods promoted by Sidney W. Mintz, who has been at the forefront of efforts to integrate the disciplines of anthropology and history for several decades and was one of the first scholars to anticipate and critique "globalization studies." Essays by leading anthropologists and historians collected here present case studies of Latin America, North America, the Caribbean, and Papua New Guinea that demonstrate the productive use of Mintz's approach.